2016
DOI: 10.1158/1940-6207.capr-15-0306
|View full text |Cite
|
Sign up to set email alerts
|

Piperlongumine Suppresses Growth and Sensitizes Pancreatic Tumors to Gemcitabine in a Xenograft Mouse Model by Modulating the NF-kappa B Pathway

Abstract: Pancreatic cancer is an aggressive malignancy, which generally respond poorly to chemotherapy. Hence, novel agents that are safe and effective are highly needed. The aim of this study was to investigate whether piperlongumine, a natural product isolated from the fruit of the pepper Piper longum, has any efficacy against human pancreatic cancer when used either alone or in combination with gemcitabine in vitro and in a xenograft mouse model. In vitro, piperlongumine inhibited the proliferation of pancreatic can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 52 publications
0
38
0
Order By: Relevance
“…PL has been tested for its synergistic anti-tumor effect in combination with TNF-related apoptosis-inducing ligand [46], ataxia telangiectasia and Rad3-related protein inhibition [50], or a chemotherapeutic agent, such as cisplatin [33, 34], paclitaxel [34], docetaxel [51], and gemcitabine [39]. Thus, we investigated the synergistic senolytic effect of PL and ABT-263 on IR-SCs.…”
Section: Resultsmentioning
confidence: 99%
“…PL has been tested for its synergistic anti-tumor effect in combination with TNF-related apoptosis-inducing ligand [46], ataxia telangiectasia and Rad3-related protein inhibition [50], or a chemotherapeutic agent, such as cisplatin [33, 34], paclitaxel [34], docetaxel [51], and gemcitabine [39]. Thus, we investigated the synergistic senolytic effect of PL and ABT-263 on IR-SCs.…”
Section: Resultsmentioning
confidence: 99%
“…Zou et al recently reported that PL interacted with thioredoxin reductase 1 to induce the ROS-mediated apoptosis of human gastric cancer cells (35). In addition, PL has been shown to promote cell death by activating several mechanisms, including apoptosis, autophagy and necrosis, affecting the PI3K/AKT/mTOR, p38/JNK, MEK/ERK and NF-κB pathways (22,(27)(28)(29)36). In the present study, we found that PL alone induced the death of pancreatic cancer cells, at least in part, by the induction of ferroptosis, the execution of which requires the accumulation of ROS in an iron-dependent manner (16).…”
Section: Discussionmentioning
confidence: 99%
“…Compound 1 and seven analogues (7)(8)(9)(10)(11)(12)(13) were obtained in moderate yields via a one-pot reaction between 6 and appropriately substituted cinnamic acids, pre-activated with pivaloyl chloride (Scheme 1, steps iii and iv, 61-72% yield) [15]. 1 H NMR coupling constants (15)(16) Hz) indicated a trans configuration around the linear α,β-unsaturated double bond.…”
Section: Chemistrymentioning
confidence: 99%
“…Compound 1 has been recently reported to be a direct STAT3 inhibitor [4], a proteasome inhibitor [5], to promote autophagy [6], and to modulate NF-κB and NF-κB-regulated gene products [7].…”
Section: Introductionmentioning
confidence: 99%